A non-randomized controlled study of total intravenous anesthesia regimens for magnetic resonance imaging studies in children - Bhuvaneswari Balasubramanian; Anila D Malde; Shantanu B Kulkarni (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: We studied the efficacy and safety of different total intravenous anesthesia used for pediatric magnetic resonance imaging (MRI). Material and Methods: Children of 1-7 years age (n = 88), undergoing MRI received a loading dose of dexmedetomidine 1 μg/kg over 10 min, ketamine 1 mg/kg, and propofol 1 mg/kg in sequence. University of Michigan Sedation Scale (UMSS) of 3 was considered an acceptable level for starting the scan. Rescue ketamine 0.25-0.5 mg/kg was given if UMSS remained <3. After the loading dose of drugs, some children attained UMSS = 4 or progressive decline in heart rate, therefore, did not receive any infusion. The rest received either dexmedetomidine (0.7 μg/kg/h) (n = 35) or propofol (3 mg/kg/h) (n = 38) infusion for maintenance. Ketamine 0.25 mg/kg was used as rescue. Sedation failure was considered if either there was inability to complete the scan at the pre-set infusion rate, or there was need for >3 ketamine boluses or serious adverse events occurred. Statistical Package for Social Sciences 20 was used for analysis. Results: Initiation of scan was 100% successful with median induction time of 10 min. Maintenance of sedation was successful in 100% with dexmedetomidine and 97.4% with propofol infusion. Recovery time (25 min v/s 30 min), discharge time (35 min v/s 60 min), and total care duration (80 min v/s 105 min) were significantly less with propofol as compared to dexmedetomidine (P = 0.002, 0.000, and 0.000, respectively). There were no significant adverse events observed. Conclusion: Dexmedetomidine 1μg/kg, ketamine 1 mg/kg, and propofol 1 mg/kg provide good conditions for initiation of MRI. Although dexmedetomidine at 0.7μg/kg/h and propofol at 3 mg/kg/h are safe and effective for maintenance, propofol provides faster recovery.